Evaluation of protein supplementation for growing cattle fed grass silage-based diets: a meta-analysis. (11th June 2014) - Huuskonen, A.; Huhtanen, P.; Joki-Tokola, E.
Abstract : The objective of this meta-analysis was to develop empirical equations predicting growth responses of growing cattle to protein intake. Overall, the data set comprised 199 diets in 80 studies. The diets were mainly based on grass silage or grass silage partly or completely replaced by whole-crop silages or straw. The concentrate feeds consisted of cereal grains, fibrous by-products and protein supplements. The analyses were conducted both comprehensively for all studies and also separately for studies in which soybean meal (SBM; n =71 diets/28 studies), fish meal (FM; 27/12) and rapeseed meal (RSM; 74/35) were used as a protein supplement. Increasing dietary CP concentration increased ( P <0.01) BW gain (BWG), but the responses were quantitatively small (1.4 g per 1 g/kg dry matter (DM) increase in dietary CP concentration). The BWG responses were not different for bulls v . steers and heifers (1.4 v . 1.3 g per 1 g/kg DM increase in dietary CP concentration) and for dairy v . beef breeds (1.2 v . 1.7 g per 1 g/kg, respectively). The effect of increased CP concentration declined ( P <0.01) with increasing mean BW of the animals and with improved BWG of the control animals (the lowest CP diet in each study). The BWG responses to protein supplementation were not related to the CP concentration in the control diet. The BWG responses increased ( P <0.05) with increased ammonia N concentration in silage N and declined marginally ( P >0.10) with increasing proportion of concentrate in the diet. All protein supplements had a significant effect on BWG, but the effects were greater for RSM ( P <0.01) and FM ( P <0.05) than for SBM. Increasing dietary CP concentration improved ( P <0.01) feed efficiency when expressed as BWG/kg DM intake, but decreased markedly when expressed as BWG/kg CP intake. Assuming CP concentration of 170 g/kg BW marginal efficiency of the utilisation of incremental CP intake was only 0.05. Increasing dietary CP concentration had no effects on carcass weight, dressing proportion or conformation score, but it increased ( P <0.01) fat score. Owing to limited production responses, higher prices of protein supplements compared with cereal grains and possible increases the N and P emissions, there is generally no benefit from using protein supplementation for growing cattle fed grass silage-based diets, provided that the supply of rumen-degradable protein is not limiting digestion in the rumen.